Analisis pengembangan model bisnis pada industri animasi menggunakan business model canvas yang terbatasi biaya - Digdoyo Oktapriandi; Muhammad Ridwan Andi Purnomo; Ali Parkhan (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
Business development is an important thing for every company in order to adjust their self tofollow the world sophistication. One of business sector is animation that now became more advance along the world development. In Indonesia the business move in the field of animation has not been so ogled by the investors. One big reason is because investors do not know the level of profit to be gained. This study aims to develop a business model company engaged in the field of animation that accompanied the information related to the benefits of investment that will be obtained. the Method used in this research are business model canvas (BMC) and SWOT analysis which being modified with cost analysis. The results obtained is